Measurement of Three-Dimensional Deformations by Phase-Shifting Digital Holographic Interferometry - Almoro, Percival; Cadatal, Marilou; Daza, Marlon Rosendo (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
Out-of-plane deformations of a cantilever were measured using phase-shifting digital holographic interferometry (PSDHI) and the Fourier transform method (FTM). The cantilever was recorded in two different states, and holograms were stored electronically with a charge-coupled device (CCD) camera. When the holograms are superimposed and reconstructed jointly, a holographic interferogram results. The three-dimensional (3D) surface deformations were successfully visualized by applying FTM to holographic interferogram analysis. The minimum surface displacement measured was 0.317 µm. The processing time for the digital reconstruction and visualization of 3D deformation took about 1 minute. The technique was calibrated using Michelson interferometry setup.